“Kreosir” (Kreasi Olahan Sirsak) Membagun Jiwa Enterpreneur Sejak Dini - Sunarti, Sunarti (Pena Edukasia, 2023)
The principal capital to become a successful entrepreneur is a strong motivation from within the individual as well as the courage to take risks, perseverance, and tenacity in running a business. Early age is a significant period in forming future patterns in children's lives. During this period, the role of parents was indispensable in shaping their lifestyle, namely by instilling religious and moral values, motivating them to study hard so that they hope that when they grow up, they can become successful people, and educating children with an entrepreneurial spirit. One way to stimulate the growth of the entrepreneurial spirit of students from an early age is through Market Day activities to market innovative soursop products that have been processed together.